Legal Problems Against the Notary Who Made a Deed of Sale and Purchase Agreement on Illegal Fishing - R. Juli Moertiono (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Law enforcement in the fisheries sector faces significant challenges with the rise of illegal fishing practices which are detrimental to marine ecosystems and the country's economy. In this context, the role of notaries as public officials who have the authority to make authentic deeds is crucial, especially when they are involved in making sale and purchase agreement deeds related to illegal activities. Legal problems arise when a notary, either intentionally or through negligence, makes a deed that facilitates illegal fishing transactions, which indirectly provides legal legitimacy to this unlawful activity. The notary's obligation to verify documents and ensure the legality of the activity that is the object of the deed is a crucial point in preventing legal violations. However, if the notary fails to carry out his obligations, this can lead to legal consequences for the notary, either in the form of administrative sanctions or criminal charges. This research aims to analyze the legal responsibilities of notaries in making sales and purchase agreement deeds related to illegal fishing, as well as exploring the legal implications and preventive steps that can be taken to prevent notaries' involvement in supporting illegal practices. Through normative analysis, this research finds that there is a need to increase supervision of notary practices and enforce strict sanctions to prevent abuse of notary authority in the context of illegal transactions.